2013
DOI: 10.1002/rcm.6784
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of co‐eluted triglycerides in the marine diatom model organism Thalassiosira pseudonana by ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry

Abstract: We put forward a hypothesis that TAGs in T. pseudonana are only derived from lipids in chloroplasts through prokaryotic biosynthesis pathway based on the precise information of sn-2 fatty acids, which is significant not only for the assessment of biofuel quality, but also for the tracing of biosynthetic precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(83 reference statements)
0
9
1
Order By: Relevance
“…found that under different collision energy (5–80 V), the abundance of ions [M + Na–R 1 COOH] + of MGDG and DGDG was always greater than that of ions [M + Na–R 2 COOH] + , respectively. The same observation was made by Li et al . that [M + Li–R 1/3 COOH] + of TAG had greater abundance than that of [M + Li–R 2 COOH] + using various collision energies (6–80 V).…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…found that under different collision energy (5–80 V), the abundance of ions [M + Na–R 1 COOH] + of MGDG and DGDG was always greater than that of ions [M + Na–R 2 COOH] + , respectively. The same observation was made by Li et al . that [M + Li–R 1/3 COOH] + of TAG had greater abundance than that of [M + Li–R 2 COOH] + using various collision energies (6–80 V).…”
Section: Resultscontrasting
confidence: 56%
“…Li et al . utilized [M + Li] + precursor ions for structural elucidation of triglycerides (TAGs) . Zhao et al .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the polar lipids, recent studies have shown that different microalgal species contain a diverse array of TAGs and these TAGs can also be used for rapidly distinguishing microalgae (Li et al. ,b). There were 12TAGs in NMBluh014 and 16 TAGs in NMBluh‐identified.…”
Section: Resultsmentioning
confidence: 99%
“…), but recent studies have shown that different microalgal species contain a diverse composition of lipids, and that these lipids can be used to rapidily distinguish microalgae (Li et al. ,b). Hence, the qualitative and semiquantitative analyses of lipids have been completed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid chromatography-mass spectrometry has been widely used for the analysis of various lipid classes [16,17]. A variety of mass spectrum techniques is available to determine the exact TAG structure of SCO [18][19][20]. The use of tandem mass spectrometric (MS/MS) analysis is crucial to identify TAG present in the lipid.…”
Section: Introductionmentioning
confidence: 99%